A decade of digital maturity models: much ado about nothing? - Tristan Thordsen; Markus Bick (Information Systems and e-Business Management, 2023)
The topic of digital maturity has evolved into a full-grown hype in the last decade. It is widely assumed that the level of an organization's digital maturity is directly linked to its performance. Digital Maturity Models (DMMs) have been designed specifically to assess an organization's digital status quo and to provide concrete measures to increase its level of digital maturity. Given this relevance, a multitude of these models have emerged. Still, the development and application of DMMs is controversially discussed within the academic community leading to great uncertainty regarding their value for both theory and practice. In this systematic literature review, we seek to paint a comprehensive picture of the research field by identifying and contrasting the main contentious opinions among IS scholars. An analysis of detailed information regarding the research area – encompassing extensive DMM literature, academic discussion, and feedback – shows that various critical voices question the actual practical and theoretical value of DMMs, underlining the absence of objective evaluation criteria of these models and pointing out the lack of empirical data to prove the suggested relationship between maturity and performance. Based on our experience in this field, we provide a first synthesis of eleven years of DMMs and derive a research agenda.
Keywords: 650; Digital maturity model; Digital transformation; Literature review